PROBLEM-ORIENTED APPROACH TO THE FORMATION OF INFORMATION SUPPORT FOR JUDICIAL AND LAW ENFORCEMENT AGENCIES - Kovalchuk, Olha; Banakh, Serhiy (Актуальні проблеми правознавства, 2024)
The article discusses the use of a prospective problem-oriented approach to shaping the information support for judicial and law enforcement agencies. The rapid development of information technologies is transforming the criminal environment. Criminals increasingly utilize the digital space, leaving numerous diverse electronic traces within it. These encompass personal information, online correspondence, phone call records, media data, browsing history, geolocation data, and more. The task of judicial and law enforcement agencies is to uncover criminal patterns through the electronic traces of offenders and provide timely intelligence information. For the effective processing of data on criminal activities, the use of quality information support by judicial and law enforcement agencies is currently an essential condition. Its formation is only possible through the application of a problem-oriented approach to data collection, storage, and analysis. The efficient operation of modern judicial and law enforcement agencies requires the utilization of cutting-edge information technologies (IT). Such technologies can ensure quality and rapid data management and transform them into useful information for making fair and transparent judicial decisions. With the exponential growth in the volume of information that judicial and law enforcement agencies need to process on a daily basis, the requirements for organizing data repositories and exchanging criminal legal information among different structures of the legal system are increasing. To establish effective information support for judicial and law enforcement agencies, it is necessary to employ new solutions, tools, and methods for data analytics and information technologies, such as artificial intelligence (AI).